Intellectual Property, Antitrust and Cumulative Innovation in the EU and the US. - Käseberg, Thorsten (Hart studies in competition law., 2012)
In this book lawyer and economist Thorsten Käseberg looks at how 'cumulative innovation' is actually accounted for under IP and antitrust laws in the EU and the US, and how it could alternatively be dealt with.